(untitled) (Global Journal of Medical Research, 2019)
Acute bleeding in the head and neck area occurs due to various causes and often is a life-threatening situation. Head and neck cancers can be a cause of intractable hemorrhage from local tumour irradiation or spontaneous tumourbleeding1. In addition to tumour-related bleeding, iatrogenic bleeding related to surgical procedures or trauma, can also lead to intractable, lifethreatening bleeding1. A pseudoaneurysm is an extravascular hematoma that communicates with the intravascular space. This rare lesion receives its name from the fact that its vascular wall is composed of fibrous connective tissue (pseudo-capsule) that develops after rupture of the endothelium2.